2013
DOI: 10.7790/tja.v63i2.414
|View full text |Cite
|
Sign up to set email alerts
|

‘They think I’m really cool and nice’: The impact of Internet support on the social networks and loneliness of young people with disabilities

Abstract: . 2013. 'They think I'm really cool and nice': The impact of Internet support on the social networks and loneliness of young people with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…A similar pattern was seen after intervention in the larger study of youth without CCN (Raghavendra et al, 2013b). There is little research using the ALSDQ in youth with disabilities and these five participants did not have high levels of loneliness to begin with.…”
Section: Discussionsupporting
confidence: 61%
“…A similar pattern was seen after intervention in the larger study of youth without CCN (Raghavendra et al, 2013b). There is little research using the ALSDQ in youth with disabilities and these five participants did not have high levels of loneliness to begin with.…”
Section: Discussionsupporting
confidence: 61%
“…Our approach, drawing on Bourdieu's theories of capital, has allowed us to identify how young people with disabilities differ from their peers who do not have disabilities in the nature and extent of Internet use. We identified that they face many barriers and facilitators: varying functional abilities in areas of physical, cognitive and literacy skills and limited offline social networks; they also face environmental factors such as limited access to appropriate assistive technology, parents' fear of their children being online and parents' low expectations of their children's online potential (Raghavendra et al, , , ; Grace et al, ). The findings also confirm previous findings among children without disabilities that home/family resources can impact on young people's IT use.…”
Section: Discussionmentioning
confidence: 99%
“…Positive outcomes have been reported for participants in both performance and satisfaction when socialising online (using games, Skype™, Chat, Facebook™, Twitter™, videos, email, Livewire™, and blogging) [46,47,50,51]. Currently, Hemsley et al [52] are investigating the use of Twitter™ for people with lifelong, acquired, and progressive physical and communication disabilities (i.e., people with: cerebral palsy; stroke; motor neurone disease) to increase information exchange and active online participation [52].…”
Section: Injury (Tbi)mentioning
confidence: 99%